Ethnic differences in the prevalence of metabolic syndrome: results from a multi-ethnic population-based survey in Malaysia - Rampal, S.; Mahadeva, S.; Guallar, E.; Bulgiba, A.; Mohamed, R.; Rahmat, R.; Arif, M.T.; Rampal, L. (Public Library of Science, 2012)
Introduction :The prevalence of metabolic syndrome is increasing disproportionately among the different ethnicities in Asia compared to the rest of the world. This study aims to determine the differences in the prevalence of metabolic syndrome across ethnicities in Malaysia, a multi-ethnic country. Methods :In 2004, we conducted a national cross-sectional population-based study using a stratified two-stage cluster sampling design (N = 17,211). Metabolic syndrome was defined according to the International Diabetes Federation/National Heart, Lung and Blood Institute/American Heart Association (IDF/NHLBI/AHA-2009) criteria. Multivariate models were used to study the independent association between ethnicity and the prevalence of the metabolic syndrome. Results :The overall mean age was 36.9 years, and 50.0 participants were female. The ethnic distribution was 57.0 Malay, 28.5 Chinese, 8.9 Indian and 5.0 Indigenous Sarawakians. The overall prevalence of the metabolic syndrome was 27.5, with a prevalence of central obesity, raised triglycerides, low high density lipoprotein cholesterol, raised blood pressure and raised fasting glucose of 36.9, 29.3, 37.2, 38.0 and 29.1, respectively. Among those <40 years, the adjusted prevalence ratios for metabolic syndrome for ethnic Chinese, Indians, and Indigenous Sarawakians compared to ethnic Malay were 0.81 (95 CI 0.67 to 0.96), 1.42 (95 CI 1.19 to 1.69) and 1.37 (95 CI 1.08 to 1.73), respectively. Among those aged â¥40 years, the corresponding prevalence ratios were 0.86 (95 CI 0.79 to 0.92), 1.25 (95 CI 1.15 to 1.36), and 0.94 (95 CI 0.80, 1.11). The P-value for the interaction of ethnicity by age was 0.001. Conclusions :The overall prevalence of metabolic syndrome in Malaysia was high, with marked differences across ethnicities. Ethnic Chinese had the lowest prevalence of metabolic syndrome, while ethnic Indians had the highest. Indigenous Sarawakians showed a marked increase in metabolic syndrome at young ages.